Particle Shape-Based Evaluation of the Leaching of Sphalerite Ore in Dilute Acid Solutions - Mert Terzi; İlgin Kurşun Ünver; Tuğba Deniz Tombal (Journal of Advanced Research in Natural and Applied Sciences)
In this study, the effects of changes in particle shapes on dissolution efficiencies in zinc (Zn) recovery from a lead-zinc (Pb-Zn) ore by acid leaching method were investigated. In the experiments with nitric acid (HNO3), sulfuric acid (H2SO4), and hydrochloric acid (HCl), particle size (75-106-150 µm), solids ratio (5-10-15-20-25%), leaching time (30-60-120-180-240 min), acid dosage (0.25-0.5-1-2-5 M) and pulp temperature (30-40-50-60-70 oC) parameters were analyzed. Optimum results were obtained under the conditions of 75 µm particle size, 15% solids ratio, 120 min leaching time, 0.5 M acid dosage, and 50°C pulp temperature for H2SO4; 106 µm particle size, 25% solids ratio, 60 min leaching time, 0.5 M acid dosage, and 70°C pulp temperature for HCl; 75 µm particle size, 20% solids ratio, 60 min leaching time, 1 M acid dosage, and 50°C pulp temperature for HNO3. As a consequence of the tests performed under these optimized conditions, 97.32%, 96.38% and 96.06% Zn dissolution efficiencies were obtained. Within the context of particle shape factor research, microscope images of the leaching residues were obtained from the experiments in which the pulp temperature, acid dosage, and leaching time parameters were examined. The samples obtained from the experiments with all three acids were compared with the ore samples, and the impacts of changes in circularity, roundness, and solidity values on dissolution efficiencies were interpreted.